Republic of Poland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This paper highlights the fact that to address the challenge of declining working age population, policies should not only aim to support fertility, but also to increase labor force participation rate, to improve labor allocation across sectors and to encourage net immigration. However, with some recent measures going in the opposite direction, even such mitigating policies may not fully offset the demographic headwinds. Poland faces profound demographic changes. The decline of fertility rate and growing life expectancy, mostly driven by longevity of older cohorts, will significantly change the demographic landscape. Demographics may soon pose a barrier for growth. The historical expansion of working age population appears to have been only partly utilized to boost potential growth, with increased unemployment and declined labor force participation rates dampening potential gains. Net migration was also a drag on the labor supply in the past, but this has changed recently. In addition to a steady outflow of permanent migrants, there was a sharp pickup in temporary migration after EU accession.